Witness onstage : documentary theatre in twenty-first-century Russia - Flynn, Molly (Theatre: theory, practice, performance, 2020)
As the Kremlin's crackdown on freedom of expression continues to tighten, Russian playwrights and directors are using documentary theatre to create space for the public discussion of injustice in the civic sphere and its connections to the country's twentieth-century past. Witness Onstage traces the history of documentary theatre's rapid growth in twenty-first century Russia and situates the form within the socio-political setting of the Putin years. It argues that through the practice of performing documents, Russian theatre artists are creating a new type of cultural and historical archive that challenges the dominance of state-sponsored media and invites individuals to participate in a collective renegotiation of cultural narratives.